Antithrombin III Alleviates Myocardial Ischemia/Reperfusion Injury by Inhibiting Excessive Autophagy in a Phosphoinositide 3-Kinase/Akt-Dependent Manner - Huang, Kai-yu; Wang, Jiao-ni; Zhou, Ying-ying; Wu, Shao-ze; Tao, Lu-yuan; Peng, Yang-pei; Que, Jia-qun; Xue, Yang-jing; Ji, Kang-ting (Frontiers in Pharmacology, 2019)
Autophagy is fundamental to myocardial ischaemia/reperfusion (I/R) injury. While antithrombin III (AT) has been shown to protect cardiomyocytes against I/R injury, whether it modulates autophagy is unknown. The objective of this study was to investigate whether AT regulates autophagy during I/R injury and, if so, the potential mechanism involved. Our study showed that AT attenuated I/R injury both in vivo and in vitro. Autophagy was increased both in H9C2 myocytes and in mouse hearts following I/R injury. Stimulation of autophagy by rapamycin attenuated the protective effect of AT against H9C2 cell injury, suggesting that autophagy is important for the protective role of AT in I/R. Furthermore, the cardioprotective effects of AT were abolished by A6730, a specific Akt inhibitor. This study showed that AT exhibits a cardioprotective effect by modulating autophagy during I/R in a phosphoinositide 3-kinase/Akt-dependent manner.